Effectiveness of problem-based learning model to improve listening skills in foreign language courses - Nurhidayati,; Muhd Zulkifli Ismail,; Machmudah, Umi; Ilyana Jalaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Strengthening the foundation of the foreign language would be more beneficial to the students to be used as the medium of instruction in certain situations. Learning a foreign language needs a different kind of language acquisition, including listening skills. Language could be a barrier to communication, whether verbal or written, when information is presented. Problem-based learning (PBL) is a student-centered learning which promotes collaboration and critical thinking through solving open-ended problems. This process of solving problem consequently drives students to be actively involved in authentic learning situation. Accordingly, this study aimed to develop a problem-based listening strategy learning model in order to facilitate the acquisition of Arabic as one of the foreign language courses at State University Malang, Indonesia. The study was conducted using observation, documentation, interview and questionnaire techniques. The design based on the research development model adapted from Willis’s R2D2 development model, this study incorporated four stages which are i) orientation of the problem, ii) organizing learning, iii) guiding individual and group investigations, and iv) analyzing and evaluating the problem-solving process. Findings accentuated the role of PBL model in the listening learning process. It increased the student involvement in listening activities and improved the learning outcomes. These findings implied that the model could be implemented in learning foreign language, especially in listening skills and this points out possible directions for more effective uptake ofin learning foreign languages.